Glaciological Aspects and Mass Budget of the Ice Sheet in Mizuho Plateau - SHIMIZU, Hiromu; WATANABE, Okitsugu; KOBAYASHI, Shunichi; YAMADA, Tomomi; NARUSE, Renji; AGETA, Yutaka (1978)
P(論文) Distributions of the glaciological and the meteorological aspects in Mizuho Plateau were plotted against the surface elevation of the ice sheet. Three boundaries common to most of the aspects were found at the elevations of 400-500m (firn line), 700-1000m (dry snow line), 1700-2100m and 3000-3200m. Glaciological zonation of the ice sheet in Mizuho Plateau was suggested. An estimation was made on the mass budget of the ice sheet in the Shirase and Soya drainage basins, Mizuho Plateau. Each mass budget appeared positive during the last several years. Approaches to determine the mass budget of the ice sheet were developed, and problems concerning its studies were pointed out. departmental bulletin paper